Online Teaching vs. Classroom Teaching in the Scenario of the Covid-19 Pandemic in India - Divya Deevi, Kavi Balabrahma Chary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Online teaching is barely twenty years old whereas classroom teaching is hundreds of years old. The purpose of both modes is the same teaching. But they are quite different from one another in their concept, structure, application and environment. Classroom teaching ruled the education sector for a long period because there was no alternative to it. Still, it has its due role. With the introduction of computer and software technology in the education field, a new style of teaching, online teaching, has been designed. Initially, it was intended to cater to the needs of a section of software people. Job seekers and promotion aspirants have found it convenient to gain knowledge in their own or new domains in their leisure time. Slowly this has found a significant place in regular education also. But the present pandemic situation has accelerated the entry of online teaching at all levels from primary education to higher education. Students face some initial troubles. They should buy sophisticated and modern devices; they should have an internet connection and there should be an uninterrupted power supply. This has become a challenge for poor people and those living in rural areas in India. However, students pursuing higher studies in Western countries have found this mode of online teaching very useful. They need not spend a lot of money and they can continue to do part-time jobs to earn money for their studies. But this online system of education does not suit the conditions prevailing in India. Still, many students are unable to follow online classes. The authorities should think carefully before issuing guidelines, keeping in view the financial and health problems of students especially, kids. The loss of time in the academic year can be compensated in many ways. When normalcy is restored all people in the education field will again switch over to classroom teaching in toto.